Compliance and the new public management as an attempt to prevent and fight corruption (Revista Brasileira Multidisciplinar, 2021)
Throughout history, notably after the world wars, models of public administration have been tested, increasingly seeking efficiency, cost control, transparency, accountability and integrity. At the same time, corruption scandals are plaguing modern societies, perplexed and suspicious. Public compliance, whose bases were obtained from a loan from corporate governance, appears as a promising option to mitigate fraud and administrative irregularities, moralizing the public service. In this sense, this work aims to analyze, through literature review, public compliance, in particular its scope, inquiring whether the implementation challenges can be overcome. Going through the systems already used, the main elements of compliance and, finally, their application to Public Law, it is concluded, at the end of the work, that the results are promising, signaling the need for cultural transformation of all social actors.
Keywords: Public Administration; Corruption; Corporate Governance; State Law; Cultural Transformation